The effect of L-glutamine on mucosal healing in experimental colitis is superior to short-chain fatty acids - Ekrem KAYA; Alper CEYLAN; Nurten KARA; Hakan GÜVEN; Levent YILDIZ (Turkish Journal of Gastroenterology, 2019)
-